Access to bank finance by MSMEs: Size and turnover effects - Samuel Tiriongo; Roselyne Njino; Hillary Mulindi (Kenya Bankers Association (KBA), 2025)
Micro, Small and Medium-sized Enterprises (MSMEs) are crucial drivers of economic growth. In Kenya, MSMEs represent about 98 percent of all businesses and contribute over 30 percent to the GDP. Despite their essential role in the economy, these enterprises face substantial challenges in accessing bank finance, thereby hindering their growth and development. On this account, this study uses Kenya Bankers Association (KBA) Inuka Impact survey 2024 data with the propensity score matching and difference in difference analysis to examine the impact of banking sector's intervention program on MSMEs ability to access bank credit. The results shows that size and turnover are critical determinants of MSMEs access to finance, and while the interventions by the Inuka program have yielded some positive results, these efforts need to be extended beyond capacity building and training to achieve a stronger and more sustainable impact. Therefore, policies aimed at supporting MSMEs in Kenya should tailored to the distinct stages of MSMEs development, ensuring that interventions are diversified and comprehensive to drive meaningful outcomes in the economy.
Keywords: 330; Lending; debt capital; SME financing; SMEs; micro-enterprises; Kenya; Kreditgeschäft; Fremdkapital; Mittelstandsfinanzierung; KMU; Kleinstunternehmen; Kenia